Cryptocurrency - Ambiguities and the impending crisis - Kumar, Alok Prasanna (Economic & Political Weekly)
Consequent to the lifting of the (3z(Bban(3y (Bimposed on the trade of crypto-assets by the Supreme Court of India, there has been a surge of interest in investing in crypto-assets from the general public, spurred by aggressive marketing campaigns by well-funded start-ups. In the absence of proper regulation, there is a very real danger that the public may be mis-sold this product with harm to the wider economy.-Reproduced s